Mga hulwarang modyul sa pagtuturo ng Pilipino sa ikalawang grado sa MSU-ILS - Mendoza, Warlita A. 1943-
This study aimed to prepare individualized instructional materials in Filipino for Grade two pupils in second language situation. The integrated approach was used to develop some specific skills in vocabulary, reading structure, and writing. The materials were composed of five modules, each containing four lessons. Forty-five pupils were used for the try-outs. After this, revisions were done on the modules and its effectiveness was assessed. It was found that the integrated approach in individualized instruction was effective.